Diversification of Aryl Sulfonyl Compounds through Ligand‐Controlled meta‐ and para‐C−H Borylation. (13th July 2022) - Wang, Yajun; Chang, Wenju; Qin, Shengmeng; Ang, Han; Ma, Jiawei; Lu, Shuo; Liang, Yong
Abstract: Aryl sulfones and aryl sulfonamides are of great importance in organic synthesis and medicinal chemistry. Although ortho ‐C−H functionalization of aryl sulfonyl compounds has been extensively explored, the functionalization of remote meta‐ and para ‐C−H bonds is very rare. Herein, we report a tunable meta‐ and para ‐selective C−H borylation of aryl sulfonyl compounds enabled by computationally designed ligands and iridium catalyst. This method is capable of accommodating a broad range of substrates under mild reaction conditions. Gram‐scale preparation can be achieved with iridium catalyst loading as low as 0.1 mol%. As the introduced boronate group can be easily converted into many other groups, our method provides a general solution to installing functional groups at either meta ‐ or para ‐position of aryl sulfones and aryl sulfonamides with good to excellent selectivity. Abstract : A tunable meta ‐ or para ‐selective C−H borylation of aryl sulfonyl compounds was enabled by the use of computationally designed ligands and iridium catalysis. The possibility to borylate these previously hardly accessible positions of aryl sulfones and aryl sulfonamides enriches the synthetic toolbox for remote C−H functionalization. Further diversifications of the introduced Bpin as well as the original sulfonyl groups were also demonstrated.